Characteristics and Trends of household carbon emissions research from 1993 to 2019: A bibliometric analysis and its implications. (1st May 2021) - Zeng, Jingjing; Qu, Jiansheng; Ma, Hanqing; Gou, Xiaohua
Abstract: The study of household carbon emissions (HCEs) has become one of the most important topics in sustainability research due to the growing awareness of its significances in responding to global warming. This paper aims to identify the trends and characteristics of HCEs research for the period 1993–2019 through the bibliometric analysis approach. The impacts of most productive journals, countries, institutions and authors are evaluated by citation analysis, while the co-authorship network between various countries, institutions as well as the co-occurrence among different keywords are presented. The results of this paper provide a detailed picture on HCEs-related articles from 1993 to 2019. Both the number of publications on HCEs and the cooperation among countries and institutions have increased during the period. Keyword analysis suggests that the revelation of current status of HCEs and corresponding influencing factors are the main lines of HCEs research, and the prediction of HCEs should become the focus of future research. The valuable results obtained from this study can help the academic professionals keep informed of the latest developments in the HCEs-related field. Highlights: We employed bibliometric analysis to examine the evolution in HCEs Research. HCEs research is at its rapid growth stage of development. USA and China are the most active countries in HCEs research. The quantification of HCEs and corresponding influencing factors are the main line. The evolution trend of HCEs should be the focus of future research.